Pengaruh Suhu dan Kelembaban Terhadap Konsentrasi Pb di Udara Kota Pontianak - Winardi (JURNAL BORNEO AKCAYA, 2014)
The existence of Lead (Pb) pollutants in the air that generated by motor vehicle exhaust emissions determined by how large the influence of temperature and humidity tend to change according to time and weather influences. Temperature and humidity Changes in the earth's surface due to solar radiation in the morning-afternoon-evening will give change in the concentration of Pb in the air. With the days variation will be seen the influence of weather that gives the difference in temperature and humidity of each day so that the concentration of Pb in air pollutants, will be varied. This research looked at the extent to which the effect of environmental factors influence, like the temperature and humidity of the Pb concentration in the air. Sampling carried out based on the variation of the morning, afternoon and evening and Sunday till Monday variation. Temperature, humidity and weather conditions were measured and observed directly in the field, while Pb concentrations were analyzed in the laboratory. The results obtained were compared with each other. The results showed that the highest concentration of Pb in the morning, because in the morning the temperature more lower at the Earth's surface and humidity tends to be high which causes pollutants become hard to diluted and difficult to dispersed vertically upwards.Until the Earth's surface temperature rises, along with the increasing of solar radiation which causes the air temperature rises and air expands so as pollutants become diluted. On rainy days where the temperature drops and the humidity rises, the Pb concentrations tend to be higher. The results that obtained also show that the traffic density factor can not be ignored and can affect the the concentration of Pb in the air.